Effect of H2S and HCl contaminants on nickel and ceria pattern anode solid oxide fuel cells. (10th August 2022) - Tabish, A.N.; Patel, H.C.; Mani, A.; Schoonman, J.; Aravind, P.V.
Abstract: In this study, with the motivation of elucidating the effect of H2 S and HCl on solid oxide fuel cell anodes, nickel and ceria pattern anodes are prepared on yttrium-stabilized zirconia electrolyte, and the effect of H2 S and HCl on their performance is tested using electrochemical impedance spectroscopy. However, it has been found that while H2 S adversely impacts both nickel and ceria, the poisoning caused is reversible for nickel and only partially reversible for ceria. Poisoning kinetics are similar and fast for both materials, while recovery kinetics are slower for ceria than nickel. High sulfur coverage is the rate-limiting factor inferred from the elementary kinetic modeling. Unlike H2 S, the presence of HCl appeared to be favorable for electrochemical oxidation as the polarization resistance of both pattern electrode cells decreased upon feeding HCl contaminated hydrogen gas. Similar behavior has not been reported previously, and the conclusion regarding underlying mechanisms requires further investigation.